2018
DOI: 10.5296/emsd.v7i2.12690
|View full text |Cite
|
Sign up to set email alerts
|

Motivators for Green Buildings: A Review

Abstract: Motivators can be defined as specific catalysts that drive people to act in a certain way. These motivators are important for promoting green buildings and have a clear impact on decision-makers to adopt and implement the green building concept in architectural practice. This paper presents a comprehensive literature review to identify the important motivators for the adoption of green buildings among the stakeholders of the construction industry, the categorization and efficiency of green building motivators,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
(116 reference statements)
0
13
1
Order By: Relevance
“…IG01 (financial benefits/reduced costs/increased property value) are also assessed significantly higher than the other four triggers. Contrary to the current study, previous studies [66,[75][76][77] confirmed that most 'green' decisions are not taken because of their benefit for the environment, but for other reasons, mainly costs; this is the second highest concern among stakeholders. The respondents have highly rated the environmental drivers of GB while the literature suggest otherwise.…”
Section: Perceived Triggers Of Gb Practices In Tanzaniacontrasting
confidence: 85%
“…IG01 (financial benefits/reduced costs/increased property value) are also assessed significantly higher than the other four triggers. Contrary to the current study, previous studies [66,[75][76][77] confirmed that most 'green' decisions are not taken because of their benefit for the environment, but for other reasons, mainly costs; this is the second highest concern among stakeholders. The respondents have highly rated the environmental drivers of GB while the literature suggest otherwise.…”
Section: Perceived Triggers Of Gb Practices In Tanzaniacontrasting
confidence: 85%
“…Achieving a healthy environment based on the efficiency of resources in the SC requires considering local regional variables due to the differences in the economic development and quality of life of the communities. Mainly, it is necessary to evaluate the characteristics of the inhabited place and its integration with the community to optimize the use of resources and eco-efficiency ensuring the proposed infrastructure's quality, economy and durability throughout the life cycle (see Figure 5) [29,35,75,76]. Thus, offering opportunities for participation and self-identity expression over large-scale consumption of standardized product [77].…”
Section: Resultsmentioning
confidence: 99%
“…People install green infrastructure to receive various benefits. Akreim and Suzer (2018), reviewed 32 studies and identified 26 factors that motivate green buildings. They have classified these factors into environmental, economic, and social motivators.…”
Section: Benefits Of Green Walls and Other Green Infrastructure As Mo...mentioning
confidence: 99%